2023
DOI: 10.1002/mp.16630
|View full text |Cite
|
Sign up to set email alerts
|

A structured FMEA approach to optimizing combinations of plan‐specific quality assurance techniques for IMRT and VMAT QA

Abstract: BackgroundMany commercial tools are available for plan‐specific quality assurance (QA) of radiotherapy plans, with their functionality assessed in isolation. However, multiple QA tools are required to review the full range of potential errors. It is important to assess their effectiveness in combination with each other to look for ways to both streamline the QA process and to make certain that errors of high impact and/or high occurrence are caught before reaching patient treatment.PurposeTo develop a structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(75 reference statements)
0
3
0
1
Order By: Relevance
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection. 20,34,35 O'Daniel et al assessed the effective risk reduction of combinations of QA methods for IMRT/VMAT treatments. 34 They showed that the MC-based secondary dose calculation was available to reduce the overall risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several present studies have been reported that combining various QA tools improves the sensitivity of error detection. 20,34,35 O'Daniel et al assessed the effective risk reduction of combinations of QA methods for IMRT/VMAT treatments. 34 They showed that the MC-based secondary dose calculation was available to reduce the overall risk.…”
Section: Discussionmentioning
confidence: 99%
“…20,34,35 O'Daniel et al assessed the effective risk reduction of combinations of QA methods for IMRT/VMAT treatments. 34 They showed that the MC-based secondary dose calculation was available to reduce the overall risk. The utilization of softwarebased QA facilitated the identification of dosimetric errors caused by small targets and heterogeneities that were not detected by conventional measurement-based QA approaches.Therefore,independent verification with DoseCHECK or other Monte Carlo codes should be an important role in lung SBRT with HT.…”
Section: Discussionmentioning
confidence: 99%
“…En esta evaluación de variación del perfil de riesgo, debe tenerse en cuenta no solamente el CC del acelerador lineal sino la combinación de todos los métodos de aseguramiento de calidad empleados como por ejemplo las verificaciones de planes. 41 A título orientativo se incluyen unas tablas con recomendaciones de frecuencias y tolerancias, de aplica-ción a los aceleradores representativos del estado de la tecnología en estos momentos en nuestro país, queremos recalcar que se trata de unas recomendaciones de mínimos. Los modelos de acelerador que pueden considerarse representativos de sus marcas son el TrueBeam® (Varian Medical Systems, Palo Alto, CA) y el Versa HD™ (Elekta AB, Stockholm,Sweden) según los colaboradores de los fabricantes consultados por el GTCCAL.…”
Section: Justificación Del Carácter Del Documentounclassified
“…The transformative influence of 3D printing technology is especially conspicuous in the realm of radiotherapy, where its applications span various treatment modalities, including photon, electron, and proton therapies [4][5][6][7]. Accurate dose verification and patient-specific quality assurance (PSQA) are becoming more important, as the complexity of radiation therapy has continuously increased, such as intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) [8,9]. This importance extends to stereotactic radiotherapy techniques like stereotactic radiosurgery and stereotactic body radiotherapy (SBRT), where ensuring precise dose delivery prior to treatment is paramount [10,11].…”
Section: Introductionmentioning
confidence: 99%